Telling Pacific lives : prisms of process - Lal, Brij V.; Luker, Vicki (ANU E Press, 2008)
"This volume of essays is an exploration of the way in which scholars from different disciplines, standpoints and theoretical orientations attempt to write life stories in the Pacific. It is the product of a conference organised by the Division of Pacific and Asian History at The Australian National University in December 2005. The aim of the conference was to explore ways in which Pacific lives are read and constructed through a variety of media: films, fiction, faction, history under four overarching themes. The first, Framing Lives, sought to explore various ways of constructing a life from a classic western perspective of birth, formation, experiences and death of an individual to other ways, for example, life as secondary to a longer genealogical entity, life as a symbol of collective experience, individual lives captured and fragmented in a mosaic of others, lives made meaningful by their implication in a particular historical or cultural web, the underlying values and world views that inform one or another approach to framing a life. The second theme, the Stuff of Life, looked at materials, methods and collaborative arrangements with which the biographer, autobiographer and recorder work, their objectives, constraints, inspirations, challenges and tricks. The third section, Story Lines, focused on formats and genres such as edited diaries, collections of writings, voice recordings, genres of biography autobiography, truth and fiction (verse, dance, novels) and the varieties and different advantages of narrative shapes that crystallise the telling of a life. The final section, Telling Lives/Changing Lives, focused on biography/autobiography and the consciousness of identity, history, purpose, lives as witness and windows, telling lives as change for those involved in the tale, the telling, the listening. The overall aim was to bring out both the generic or universal challenges of telling lives as well as to highlight the particular tendencies and trends in the Pacific. Yet these four themes, which seemed analytically promising at the outset, proved in practice difficult to disentangle from the presentations at the workshop"--Provided by publisher